2021
DOI: 10.1002/gch2.202000107
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐Functionalized Recycled Polyethylene Terephthalate Nanofibrous Membrane for Sustainable On‐Demand Oil‐Water Separation

Abstract: The preservation of marine ecosystems is one of the most severe challenges at present. In particular, oil‐water separation from oil spills and oily wastewater is important. For this reason, a low‐cost, effective, and sustainable polymeric solution is in high demand. In this work, a controlled‐wettability membrane for selective separation of oil‐water mixtures and emulsions is developed. The nanofibrous membrane is prepared via a facile and cost‐effective electrospinning technique using environmentally sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Difficulties in melting the polymers [28,29] Recent studies have demonstrated the possibility of turning plastic waste into submicron fibers using the electrospinning technique [25][26][27]. Electrospinning seems to be an easy and cheap technique used to fabricate nanocomposite textile with a highly porous structure suitable for a wide variety of applications.…”
Section: Mechanical Methods Fibersmentioning
confidence: 99%
“…Difficulties in melting the polymers [28,29] Recent studies have demonstrated the possibility of turning plastic waste into submicron fibers using the electrospinning technique [25][26][27]. Electrospinning seems to be an easy and cheap technique used to fabricate nanocomposite textile with a highly porous structure suitable for a wide variety of applications.…”
Section: Mechanical Methods Fibersmentioning
confidence: 99%
“…A natural polymer, chitosan, is most often used not in its pure form but only for the modification of cellulose [ 118 ] and synthetic polymers—for example, polyethylene terephthalate [ 119 ], polycaprolactone [ 120 ], polyvinylidene fluoride [ 121 ], and polysulfone [ 122 ]. Such a modification makes it possible to increase the hydrophilicity of the membranes, which means to increase their resistance to contamination in the process of separating oil-water emulsions and to increase the stability of indicators over time.…”
Section: Commercial Polymer Membranesmentioning
confidence: 99%
“…Kusumocahyo et al further developed a lower-MWCO ultrafiltration membrane with improved permeate flux and rejection [ 681 , 682 ]. In moving forward, recycled PET was used to prepare membranes for oil-water separation [ 683 , 684 ], NF [ 685 ], and air NF [ 686 ]. To maximize their industrial implementation, scaling up into hollow fiber configuration is crucial for long-term sustainable development.…”
Section: Emerging Randd On Hollow Fiber Membranesmentioning
confidence: 99%